Blood-mimicking delivery in polygonal structure of inner quadrupletip microneedle with valveless micro-pump - MD, Ibrahim; YS, Yunos; ARH, Rigit; NAA, Mohtadzar; N, Watanabe; Y, Sunami; MRA, Rahman; LK, Wong; MZ, Mohtar (IOP Publishing Ltd., 2017)
This paper presents a titanium quadrupletip micro-needle integrated with a micropump with different inner designs, length and diameter of the micro-channels to measure and maximize the velocity flow in the micro-needle as blood delivered into human body. Titanium is used as the material of the micro-needle which are also the common material in manufacturing of micro-needle. The advancement of micro-needle technologies is improved in penetrating human outermost skin, stratum corneum and further to human blood vessels. The micro-needles with channel inner design of circular, square, hexagon, and dodecagon with quadruple tip designs are drawn with inner diameter parameter of 150μm and 100μm with two different channel length which are 10mm and 25mm. The characteristics of blood delivery in geometrically changed inner designs affect the output velocity in microneedle when the micropump is operating. The results showed that, when it is pumped at 0.04m/s, the blood velocity improved by 5.6% than when the pump is increased by 30% of its capacity. This is due to the backflow generated in the micropump.